(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This study investigated the therapeutic potential of transcranial magnetic stimulation (TMS) in the management of migraine. Migraine is a widespread neurological disorder, affecting approximately 12–15% of the global population, and is characterized by recurrent severe headache attacks. Due to the unclear pathogenesis of the disease, conventional treatments often fail to provide consistent results. In this study, repeated TMS therapy was applied to 14 patients (4 men, 10 women; mean age 38.8 ± 10.2 years) who had previously shown insufficient response to medication. Stimulation was performed using the “Dyo MAG XT” device over a 10-day period. Post-treatment analysis revealed a 33.4% reduction in the monthly frequency of migraine attacks, a 7.3% decrease in headache intensity, and a 34.7% reduction in depression scores. These results confirm that TMS is a safe and effective intervention, although further research is required to clarify its role in migraine prevention.